Dimensions of social support in the experience of work engagement in middle age:a Northern Finland Birth Cohort 1966 study - Kiema‐Junes, H. (Heli); Saarinen, A. (Aino); Muukkonen, H. (Hanni); Väyrynen, S. (Seppo); Ala‐Mursula, L. (Leena); Hintsanen, M. (Mirka) (John Wiley & Sons, 2020)
Abstract So far, the relationship between the various dimensions of social support and work engagement has not been widely examined in the literature. In this study, we examined the relationship of social support at work (from a colleague or supervisor) and social support in one’s private life (from a spouse, relative or friend) with various dimensions of work engagement (vigor, dedication and absorption). The participants (N = 5,259–5,376, 46 years‐old, 52.7% women) came from the Northern Finland Birth Cohort 1966 study. Social support was evaluated with the Social Support Questionnaire (SSQ), and work engagement was assessed with a short version of the Utrecht Work Engagement Scale (UWES‐9). The data were analyzed using linear regression analyses. The results showed that high social support at work (p < 0.001) and in one’s private life (p < 0.001) were associated with higher total work engagement, higher vigor, higher dedication, and higher absorption. These findings were adjusted for gender, marital status, education and occupational status. The results were essentially unchanged when they were additionally adjusted for job strain and effort‐reward imbalance. To conclude, our findings indicate that the experience of overall social support may play a role in the experience of work engagement.